2014
DOI: 10.11622/smedj.2014118
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoxaemia can predict unfavourable clinical outcomes in individuals with pulmonary embolism aged over 40 years

Abstract: INTRODUCTION Acute pulmonary embolism (APE) is an urgent clinical condition that can progress in a wide variety of ways. Therefore, we sought to develop an easy-to-apply algorithm, to be based on readily available clinical indicators, effective in predicting unfavourable outcomes. METHODSThis was a retrospective cohort study based on systematically collected data in a database. The study included 102 patients with APE who were admitted to a tertiary care hospital. The following outcomes were defined as unfavou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(34 reference statements)
0
0
1
Order By: Relevance
“…Our multivariate analyses showed that HR >100/min (P=0.009) and SpO 2 <90% (P=0.038) were significant risk factors for PE-related unfavorable outcome. Souza et al have also reported that SpO 2 <90% is one of the most accurate predictors of unfavorable outcome [25]. However, the present study revealed that there was no statistically significant relationship between pre-exiting comorbidities, including cardiovascular and respiratory system, and PE-related unfavorable outcome.…”
Section: Discussioncontrasting
confidence: 68%
“…Our multivariate analyses showed that HR >100/min (P=0.009) and SpO 2 <90% (P=0.038) were significant risk factors for PE-related unfavorable outcome. Souza et al have also reported that SpO 2 <90% is one of the most accurate predictors of unfavorable outcome [25]. However, the present study revealed that there was no statistically significant relationship between pre-exiting comorbidities, including cardiovascular and respiratory system, and PE-related unfavorable outcome.…”
Section: Discussioncontrasting
confidence: 68%